Prinsip Pemanfaatan Ruang Angkasa berdasarkam The OST 1967 dan Impelemntasinya terhadap Kasus Penggunaan Anti Satelit oleh India - Rizki Dwi Widyadhi; Neni Ruhaeni (UNISBA Press, 2024)
In principle, the use of outer space is free and open to all countries in the world without discrimination in accordance with Article 1 of the Outer Space Treaty 1967. According to Bin Cheng, space law is a series of international legal regulations that regulate the exploration and exploitation of outer space. including the moon and the celestial bodies in it. The Outer Space Treaty is an international agreement which aims to regulate rights and obligations, as well as prohibitions and permits in the exploration and exploitation of outer space and the celestial bodies in it. All types of activities are permitted as long as they are carried out for peaceful purposes. Use of outer space for military purposes is not permitted as regulated in Article 4 of the Outer Space Treaty. India's testing of the PDV-MK II anti-satellite ballistic missile by the Defense Research and Development Organization (DRDO) was deemed to have violated the provisions of the Articles of the Outer Space Treaty 1967. The formulation of the problem in this research is as follows: